Egocentric speech in the works of Vygotsky and Piaget: educational implications and representations by teachers - Sasso, Bruna Assem [UNESP]; Morais, Alessandra de [UNESP] (My University, 2014)
This paper presents an applied qualitative and quantitative study and seeks to understand egocentric speech according to Vygotsky and Piaget and, through a literature review, the educational implications of Vygotsky and Piaget’s ideas. Additionally, the representations of these ideas by fifteen teachers of basic education are investigated. It is important to understand egocentric speech in Vygotsky and Piaget. Despite the differences in how they conceive its nature, functions and implications, for both, egocentric speech is intrinsically linked to and facilitates our understanding of child development. Regarding the representation of teachers who criticized children who used egocentric language, when teachers established any negative consequences of such language, they attributed it to the affective and moral aspects as well as to cognition. However, their approach was more practically oriented than those found in the psychological theories addressed. Therefore, this study aids in understanding the limits and scope of teacher-training courses.